Oasis and simoon; the account of a journey through Algeria and Tunisia ... - Ossendowski, Ferdynand Antoni (Breath of the desert, 1927)
Sur les Mozabites p. 49-53
Keywords: Récits de voyage -- Mzab

Les puritains du désert. I La route du Mzab - Chevrillon, André (Revue des Deux Mondes, 1927)
Keywords: Récits de voyage -- Mzab

In the Mzab - Steele, Daniel Wilbur (Harper's Magazine, 1922)
Keywords: Récits de voyage -- Mzab

Camping in the Sahara - Hull, E.M. (Dodd, Mead and Company, 1927)
p. 53 : The Mozabites p. 167 : Ouargla and a night march
Keywords: Récits de voyage -- Mzab

The Mysterious M'Zab - Bodley, R.V.C (Wide World Magazine, 1929)
Keywords: Récits de voyage -- Mzab

Les puritains du désert (Sud-Algérien) - Chevrillon, André (Plon, 1927)
Keywords: Récits de voyage -- Mzab

D'Alger à Ghardaïa. La page d'album - Irriera, Roger (Terre d'Afrique illustrée, 1926)
Keywords: Récits de voyage -- Mzab

Nos soeurs musulmanes : scènes de la vie du désert - Célarié, Henriette (Librairie Hachette, 1925)
Keywords: Récits de voyage -- Mzab

Circuits sahariens: Laghouat, Le M'Zab, Mettlili des Chambas - Bonneval, Léon Paul Marie Deshayes de (Fédération des Syndicats d'Initiative de tourisme d'Algérie, 1925)
Chapitre 2 : Le M'zab et les M'zabites p. 29-102
Keywords: Récits de voyage -- Mzab

Les Premières oasis et le M'zab - Rozet, Georges (Horizons de France, 1929)
Keywords: Récits de voyage -- Mzab